ANALISIS PRODUKSI DAN PEMASARAN KOMODITI PISANG DI KAWASAN PANTAI UTARA MANOKWARI - Kayukatui, Risda; Mamboai, Hans; Darmawanto Uria (Sosio Agri Papua, 2023)
The purpose of this study was to (1) determine the level of production and productivity of bananas in Sairo, Bremi and Yoom 1 Villages, North Manokwari District, Manokwari Regency. (2) Analyze the income level of banana farming in Sairo, Bremi and Yoom Village 1, North Manokwari District, Manokwari Regency (3) Analyze margins, profits (Profit), share margin and marketing efficiency of bananas in Sairo, Bremi and Yoom Village 1, North Manokwari District, Regency Manokwari. The method used in this study is a qualitative description method. This method is a research method that utilizes qualitative data and then describes it descriptively and displays the results of the data as it is without any manipulation or other treatment. The conclusions from research on the production and marketing of banana commodities are (1) the total production and productivity of banana fields in Sairo, Bremi and Yoom I villages in a month, namely the average banana production is 44 kg/month or 12 bunches/month and the average land productivity of 2.83 tons/ha/month. (2) with an average cash income of IDR 724,946 and an average total income of IDR 1,150,348. (3) Margin analysis on channel I is IDR 0, profit (profit) is IDR 1,063,429, share margin is 100% and efficiency is 4.52%. Channel II is IDR 10,000, profit is IDR 7,000, share margin is 50% and efficiency is 9.91%. Channel III is IDR 30,000, profit (Profit) is IDR 11,283, share margin is 25% and efficiency is 9.13%.